1996
DOI: 10.1021/jo9605814
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intramolecular Addition/Cyclizations of Sulfonamide Anions with Alkynyliodonium Triflates. Synthesis of Dihydropyrrole, Pyrrole, Indole, and Tosylenamide Heterocycles

Abstract: The synthesis of dihydropyrroles, pyrroles, and indoles through [3-atom + 2-atom] combination of ethyl or aryl tosylamide anions with phenyl(propynyl)iodonium triflate, and the base-mediated intramolecular bicyclization of alkynyliodonium-bearing tosylamide or tosylimide substrates to furnish bicyclic and tricyclic tosylenamide (-enimide) products, is described. A detailed discussion of the scope, limitations, byproduct formation, and the basis for observed diastereoselectivity is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 38 publications
0
68
0
2
Order By: Relevance
“…Initially we focused our attention on the reaction of metalated amides with alkynyl (phenyl)iodonium salts (eq 1). 9 Stang 10 and Feldman 11 have shown that this process provides an excellent route to "push-pull"-type ynamides (4, Z = COR, CO 2 R, SO 2 Ar, etc. ), and more recently Witulski and Rainier have extended this chemistry to the preparation of ynamides where Z = hydrogen, TMS, and phenyl.2a -d ,4b Unfortunately, this approach is not applicable to the synthesis of ynamides in which Z is a simple alkyl group.…”
mentioning
confidence: 99%
“…Initially we focused our attention on the reaction of metalated amides with alkynyl (phenyl)iodonium salts (eq 1). 9 Stang 10 and Feldman 11 have shown that this process provides an excellent route to "push-pull"-type ynamides (4, Z = COR, CO 2 R, SO 2 Ar, etc. ), and more recently Witulski and Rainier have extended this chemistry to the preparation of ynamides where Z = hydrogen, TMS, and phenyl.2a -d ,4b Unfortunately, this approach is not applicable to the synthesis of ynamides in which Z is a simple alkyl group.…”
mentioning
confidence: 99%
“…However, an unanticipated result upon exploration of some routine indole formation chemistry provided the conceptual refocusing necessary to connect 2 to alkynyliodonium salt chemistry. 13 Exposure of tosylanilide (55) to base and then propynyl(phenyl)iodonium triflate furnished the expected indole product 57 via the presumed intermediacy of alkylidenecarbene 56. However, lesser amounts of a highly colored material whose spectral characterization led to the structural assignment 59 were identified as well.…”
Section: Methodsmentioning
confidence: 99%
“…The first example was reported by Stang and co-workers in 1994, but this transformation was limited to the synthesis of push-pull ynamines (Scheme 2.6, A [56]). An important breakthrough was reported by Feldman and co-workers [57] and Witulski and co-workers [58], who demonstrated that alkynyliodonium triflates could be used for the synthesis of more stable ynamides (Scheme 2.6, B). The first efficient synthesis of this fascinating class of compounds allowed their widespread use in organic synthesis, especially in metal-catalyzed cycloisomerization and cycloaddition reactions [59].…”
Section: Alkynylation Of Oxygen and Nitrogen Nucleophilesmentioning
confidence: 99%